Adolescents with Persistent History of Maltreatment Fail in Antisaccadic Task - Jost, Jiri; Havlisova, Helena; Bilkova, Zuzana; Stefankova, Zuzana; Zemkova, Ludmila (Journal of child & adolescent trauma, 2018)
The antisaccadic task is sensitive to what is called frontal dysfunction, i.e. dysfunction of the frontal lobes of the cerebral cortex which are the basis for a wide range of symptoms. The present study examined saccadic eye movements in adolescents with persistent history of maltreatment. Participants included 17 female subjects with maltreatment history. The control group consisted of 54 typically developing female subjects. All participants were administered Child Behavior Checklist (CBCL) and saccadic eye movement tests. CBCL showed significant differences between the maltreated and control groups. The prosaccadic test revealed insignificant results between both groups. The antisaccadic test revealed a highly significant difference (longer latencies, more prosaccadic mistakes in the group of maltreated subjects). Antisaccadic eye movements may be regarded as a possible indicator of persistent maltreatment and following emotional and behavioral problems and may therefore enhance diagnostic methods.
Keywords: Maltreatment; Frontal dysfunction; Disinhibition; Out-of-home care; Antisaccades